AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN READING COMPREHENSION AT SMA NEGERI 4 PEMATANGSIANTAR - Siahaan, Dita Agnes; Simatupang, Feby Valent; Sianipar, Taruli Florenza; Damanik, Trimasara (Transpublika Publisher, 2022)
There are four English skills that must be mastered by every student, reading is one of the most important skills to learn and master because through reading activities students can absorb the information the author wants to convey through reading texts. Reading is not just the ability to say words or sentences, but must be able to interpret the essence of the text. But in reality, students are less able to process, understand, and absorb information from what they have read. This research used qualitative data. This research was conducted on students of X PMIA 7 Students of SMA Negeri 4 Pematangsiantar in January 2022. The reason the researcher chose this class as the research subject was because they were detected as having difficulty in reading comprehension. The technique of collecting the data were interviews. The result of the research showed that some difficulties that studet’s faced in reading comprehension were difficult to understand the meaning of word, difficult to understand long sentence, difficult to determining the main idea, difficult to understand the grammar, difficult in inferencing.